Editorial - Hayes, Grahame (PINS-Psychology in Society, 2026)
It is just over three and a half years since the formation of PsySSA, and the "formal" ending of organisational divisions amongst psychologists. It is also just over three years since the first democratic elections, and the “formal" ending of political divisions amongst the citizens of this country. The divisiveness of the apartheid past still lurks in all these new formations, regardless of the "good intentions" of creating democratic, non-racial, and non-sexist institutions. Social practices are historically enduring, and hence we should not be lulled into complacency by the political praise-singing that goes along with the formation of every “new thing” in the new South Africa. A new South Africa can only truly come into being by facing the past so that it can be transcended, rather than forgotten or repressed. As Edward Said reminds us, intellectuals are emigrants in their own countries. The position of the intellectual is one of exile, an insider view from "outside". Psychologists the world over, and especially in this country, have been reluctant intellectuals (of the discipline), and more comfortable in their roles as professionals.